Preparation of Molecularly Imprinted Electrochemical Sensors and Analysis of the Doping of Epinephrine in Equine Blood - Zhao Wang; Yanqi Li; Xiaoxue Xi; Qichao Zou; Yuexing Zhang (Sensors)
In this paper, a novel molecularly imprinted polymer membrane modified glassy carbon electrode for electrochemical sensors (MIP-OH-MWCNTs-GCE) for epinephrine (EP) was successfully prepared by a gel-sol method using an optimized functional monomer oligosilsesquioxane-Al2O3 sol-ITO composite sol (ITO-POSS-Al2O3). Hydroxylated multi-walled carbon nanotubes (OH-MWCNTs) were introduced during the modification of the electrodes, and the electrochemical behavior of EP on the molecularly imprinted electrochemical sensors was probed by the differential pulse velocity (DPV) method. The experimental conditions were optimized. Under the optimized conditions, the response peak current values showed a good linear relationship with the epinephrine concentration in the range of 0.0014–2.12 μM, and the detection limit was 4.656 × 10−11 M. The prepared molecularly imprinted electrochemical sensor was successfully applied to the detection of actual samples of horse serum with recoveries of 94.97–101.36% (RSD), which indicated that the constructed molecularly imprinted membrane electrochemical sensor has a high detection accuracy for epinephrine in horse blood, and that it has a better value for practical application.